Mental Maps in the Era of Détente and the End of the Cold War 1968–91
XI, 259 p.
Keywords: Mental Maps in the Era of Détente and the End of the Cold War recreates the way in which the revolutionary changes of the last phase of the Cold War were perceived by fifteen of its leading figures in the West, East and developing world.